A Collaborative Approach between Students and Lecturers to Build Sustainable Leadership - Leiliyanti, Eva; Diyantari, Diyantari; Sa-idi, Amini; Fatkhiyati, Nurrahma Restia; Tesaannisa, Tesaannisa; Mardiana, Rizdika; Izzati, Syifaa Fadhilah; Syalika, Muthia Kafa; Tsurayya, Fasya Rakha (Universitas Muhammadiyah Malang, 2026)
To address the growing demand for globally competent and sustainability-oriented leadership, Universitas Negeri Jakarta (UNJ), Indonesia, and Prince of Songkla University (PSU), Thailand, implemented a collaborative community service program integrating intercultural exchange, leadership training, and civic engagement. The initiative aimed to strengthen cross-cultural understanding, leadership capacity, and sustainable practices among students and faculty. The program consisted of EDUBRIDGE in Pattani, RISE Initiatives in Hatyai, and a Building Leaders Seminar in Jakarta, which consolidated and reflected on the Thailand-based activities. Grounded in Experiential Learning Theory (Kolb, 1984) and Transformational Leadership Theory (Burns, 1978), the program employed interactive workshops, design thinking, leadership simulations, and immersive English camps. Six UNJ delegates collaborated with PSU counterparts to design and facilitate activities. Outcomes included improved leadership competence, intercultural communication, empathy, and problem-solving skills, alongside increased confidence in applying leadership concepts to community challenges. The program also strengthened institutional partnerships and international engagement. Overall, this initiative demonstrates the transformative potential of sustained international academic collaboration in cultivating sustainable leadership.